(untitled) (FUDMA JOURNAL OF SCIENCES, 2022)
The phenotypic traits in offspring’s are often dependent on that of the parents. Taking height as the phenotypic trait, we can obtain a regression model for parents and their offspring’s, and also test for the significance of the overall model. As the detection of causal links between genetic and phenotypic variation is accelerating, a re-examination for our conceptual tools may help by finding unifying principles within the swarm of data. The analysis from this research reveal that Multiple Correlation Coefficient is 0.87 which implies that there is a strong positive relationship between Offspring’s Growth and Parent’s Phenotype with R-squared value of 0.75 which implies that 75% of Offspring’s attribute will result from Parent Phenotype. A Multiple Regression model given as offspring’s Growth = 58.589 + 0.535Father’s Height +0.140Mother’s Height.The value 0.535 implies the contribution per unit change of Father’s Height in Offspring’s Growth and 0.140 is the contribution per unit change of Mothers Height in Offspring’s Growth. The Multiple Regression model is statistically significant with p-value of 0.003 less than 0.05. Multicolinearity test in the analysis shows that the predictor variables are moderately Collinear observing the Variance Inflation Factor (VIF). The recommendations require parents to put more efforts on preventing negative phenotypic traits from transferring from the environment to their offspring and couples should try to check their Genotype and Blood group since they highly contribute to the Offspring characteristics